Comparison of potassium and sodium content in diet and non-diet soft drinks by using capillary electrophoresis with capacitively coupled contactless conductivity detection - Guimarães, Ivanilce Cristina; da Silva, José Alberto Fracassi; de Jesus, Dosil Pereira (Eclética Química, 2009)
Capillary electrophoresis (CE) with capacitively coupled contactless conductivity detection (C4D) was used for determination of sodium and potassium concentrations in diet and non-diet soft drinks. Higher sodium concentrations were found in the diet samples due to the utilization of sodium salts of cyclamate and saccharine as sweeteners. The CE-C4D method can be used by food industries and health regulatory agencies for monitoring sodium and potassium content, not only in soft drink but in many others food products.